Epitope Lability of Phosphorylated Biomarkers of the DNA Damage Response Pathway Results in Increased Vulnerability to Effects of Delayed or Incomplete Formalin Fixation. (May 2023) - Wiseman, Elizabeth J.; Moss, Jennifer I.; Atkinson, James; Baakza, Hana; Hayes, Emily; Willis, Sophie E.; Waring, Paul M.; Rodriguez Canales, Jaime; Jones, Gemma N.
Phosphorylated biomarkers are crucial for our understanding of drug mechanism of action and dose selection during clinical trials, particularly for drugs that target protein kinases, such as DNA-damage-response (DDR) inhibitors. However, tissue fixation conditions needed to preserve DDR-specific phospho-biomarkers have not been previously investigated. Using xenograft tissues and tightly controlled formalin fixation conditions, we assessed how preanalytical factors affect phosphorylated DDR biomarkers pRAD50(Ser635), ɣH2AX(Ser139), pKAP1(Ser824), and non-phosphorylated biomarkers cMYC and ATM. Cold ischemia times ranged from 15 min to 6 hr, and the fixation duration ranged from 24 hr to 4 weeks. Epitopes pRAD50 and pKAP1 appeared the most labile assessed with staining loss after just 15 min of cold ischemia time, while ATM was more robust showing consistent expression up to 1 hr of cold ischemia. Notably, ɣH2AX expression was lost with formalin fixation over 48 hr. The use of core needle biopsies where possible and novel fixation methods such as the 2-step temperature-controlled formalin approach may improve phosphorylated biomarker preservation; however, practical challenges may affect wider clinical application. The most essential tissue-processing step when downstream analysis includes DDR phosphorylated biomarkers is immediate tissue submersion in formalin, without delay, upon excision from the patient, followed by room temperature fixation for 24 hr.